2023
DOI: 10.1177/15459683231166940
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Combined and Single Neurostimulation and Traditional Dysphagia Therapies for Post-Stroke Dysphagia: A Network Meta-Analysis

Abstract: Background Comparative therapeutic benefits of combined and single neurostimulation therapies including neuromuscular electrical stimulation (NMES), pharyngeal electrical stimulation (PES), repetitive transcranial magnetic stimulation (rTMS), transcranial direct current stimulation (tDCS), and traditional dysphagia therapy (TDT) remain unknown in post-stroke dysphagia (PSD) rehabilitation. Therefore, we performed the first network meta-analysis (NMA) to determine comparative effectiveness of combined and singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Of the 19 studies included in the analysis, eight SRs investigated the effectiveness of rTMS on post-stroke dysphagia rehabilitation ( Liao et al, 2017 ; Papadopoulou et al, 2018 ; Yang et al, 2021 ; Li H. et al, 2022 ; Qiao et al, 2022 ; Wen et al, 2022 ; Xie et al, 2022a ; Hsiao et al, 2023 ) and 11 investigated various therapeutic methods on the topic, including rTMS ( Yang et al, 2015 ; Pisegna et al, 2016 ; Bath et al, 2018 ; Chiang et al, 2018 ; Cheng et al, 2021 ; Li et al, 2021 ; Wang et al, 2021 ; Balcerak et al, 2022 ; Tan et al, 2022 ; Zhu and Gu, 2022 ; Banda et al, 2023 ). For the specific focus of this umbrella review, from the latter studies, only the information pertaining to the use of rTMS for the treatment of dysphagia post-stroke was analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 19 studies included in the analysis, eight SRs investigated the effectiveness of rTMS on post-stroke dysphagia rehabilitation ( Liao et al, 2017 ; Papadopoulou et al, 2018 ; Yang et al, 2021 ; Li H. et al, 2022 ; Qiao et al, 2022 ; Wen et al, 2022 ; Xie et al, 2022a ; Hsiao et al, 2023 ) and 11 investigated various therapeutic methods on the topic, including rTMS ( Yang et al, 2015 ; Pisegna et al, 2016 ; Bath et al, 2018 ; Chiang et al, 2018 ; Cheng et al, 2021 ; Li et al, 2021 ; Wang et al, 2021 ; Balcerak et al, 2022 ; Tan et al, 2022 ; Zhu and Gu, 2022 ; Banda et al, 2023 ). For the specific focus of this umbrella review, from the latter studies, only the information pertaining to the use of rTMS for the treatment of dysphagia post-stroke was analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the impact on swallowing ability, 12 studies reported large effects of rTMS compared to control conditions ( Yang et al, 2015 ; Liao et al, 2017 ; Chiang et al, 2018 ; Li et al, 2021 ; Wang et al, 2021 ; Li H. et al, 2022 ; Qiao et al, 2022 ; Tan et al, 2022 ; Wen et al, 2022 ; Xie et al, 2022a ; Zhu and Gu, 2022 ; Banda et al, 2023 ), two studies found moderate effects ( Pisegna et al, 2016 ; Cheng et al, 2021 ), one study found marginal effects ( Yang et al, 2021 ) and one study reported that rTMS improved swallowing ability -however, the finding could be due to chance, considering no subgroup differences and heterogeneity ( Bath et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations